Influence of CYP2D6 activity on the pharmacokinetics and pharmacodynamics of a single 20 mg dose of ibogaine in healthy volunteers - Glue, Paul; Winter, Helen; Garbe, Kira; Sonntag, Hannah; Lyudin, Alexander; Lenagh‐Glue, Zoe; Hung, C. Tak (Journal of clinical pharmacology, 2015)
Conversion of ibogaine to its active metabolite noribogaine appears to be mediated primarily by CYP2D6. We compared 168 hours pharmacokinetic profiles of both analytes after a single oral 20 mg dose of ibogaine in 21 healthy subjects who had been pretreated for 6 days with placebo or the CYP2D6 inhibitor paroxetine. In placebo-pretreated subjects, ibogaine was rapidly converted to noribogaine. Median peak noribogaine concentrations occurred at 4 hours. Compared with placebo-pretreated subjects, paroxetine-pretreated subjects had rapid (Tmax = 1.5 hours) and substantial absorption of ibogaine, with detectable levels out to 72 hours, and an elimination half-life of 10.2 hours. In this group, ibogaine was also rapidly converted to noribogaine with a median Tmax of 3 hours. Extent of noribogaine exposure was similar in both groups. CYP2D6 phenotype was robustly correlated with ibogaine AUC0-t (r = 0.82) and Cmax (r = 0.77). Active moiety (ibogaine plus noribogaine) exposure was ∼2-fold higher in paroxetine-pretreated subjects. Single 20 mg ibogaine doses were safe and well tolerated in all subjects. The doubling of exposure to active moiety in subjects with reduced CYP2D6 activity suggests it may be prudent to genotype patients awaiting ibogaine treatment, and to at least halve the intended dose of ibogaine in CYP2D6 poor metabolizers.
Gesehen am 10.06.2020